Երեխայի ծնունդը հայոց կրօնական ու ժողովրդական աւանդոյթների համապատկերում - Դալլաքյան, Լիանա (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
В статье кратко рассматривается значение деторождения в системе армянских христианских брачных традиций. Приведены примеры предпочтения рождения сына, а также представлены их религиозные и народные основы. Идея рождения сына настолько глубоко укоренилась в армянской среде, что зачастую становилась причиной множества семейных проблем. Женщина, родившая ребенка мужского пола, пользовалась гораздо большим уважением, чем та, кто рожала только девочек. Вследствие чего были нарушены христианские нормы брака. Мужчины, страстно желавшие иметь сына, могли привести домой другую женщину, что ущемляло права законной супруги. Рассматривая подобные проявления семейно-супружеских отношений, приходим к выводу, что христианская религиозная система ценностей определяет в браке принцип «одна женщина — один мужчина», что является важнейшим условием крепкой, гармоничной семьи. The article discusses the idea of giving birth to a male child in the context of the Armenian Christian marriage traditions. Several examples given in the article come to present the preference of giving birth to a male child. The idea of giving birth to a male child was so deeply rooted in the Armenian reality that it, in its turn, caused numerous marriage problems. The women giving birth to a male child were held in higher esteem than women giving birth to a female child. As a result, the Christian norms of marriage were violated. Men who were eager to have a son could bring home another woman, which infringed on the rights of the legitimate wife. Considering such manifestations of family and marital relationships, we conclude that the Christian religious system of values defines the principle of “one woman—one man” in marriage, which is the most important condition for a strong, harmonious family.